FEATURES OF DENTAL STATUS AND SOME MICROBIOLOGICAL PARAMETERS OF THE ORAL CAVITY OF YOUNG MEN. - Y.Y. Vodoriz; N.M. Ilenko; N.V. Ilenko; T.O. Petrushanko (Ukrainian Medical Stomatological Academy, 2015)
Normal oral microflora plays an important role in the protection of human organism from disease. Oral cavity can be attributed to one of the ideal habitat for living organisms of the human body. This habitat is subdivided into several subbiotops considering the anatomical structure and other characteristics of parts of the oral cavity such as gingival sulcus, gingival and periodontal pockets. The species composition of subbiotops` microflora directly depends on the protection of local and general factors. Every person`s oral cavity, besides its natural inhabitants (flora presented with lacto-and bifidobacterias) is presented with opportunistic and pathogenic microorganisms. Violation of quantitative relationships between normal and opportunistic flora leads to dysbiotic states and to decreasing of laktoand bifidobacterias ammount and growing of opportunistic microorganisms. The aim of the study was to analyze the relationship between the parameters of dental status, oral hygiene condition and some microbiological parameters of young men. The important role of microbial factor in the etiology and pathogenesis of inflammatory periodontal diseases determines the relevance of research in this area. We examined 20 students men of III and V year of study of the Stomatological faculty of the HSEE of Ukraine "Ukrainian Medical Stomatological Academy" aged from 19 to 24 . Analysis of the performance carried differentiated depends on the course of study (1 group - students of the third year, Group 2 - students of the fifth year of study). All examined patients, did not have any complaints of oral health. Also anamnestic data was checked. Objective dental examination was performed using a standard set of dental tools and periodontal probes. Condition of hard tissue of teeth, periodontal tissues were diagnosed according to the main clinical techniques such as inspection, sensing, percussion, palpation. We determined the prevalence and intensity of caries. Quantitative assessment of periodontal status was performed using special indices. We used papillary- marginally-alveolar index PMA by Parma and comprehensive periodontal index. Interdental hygienic index, the index of hygienic condition of the tongue by Ulitovsky and index WTC used for determination of oral hygiene. During the experiment we determined the adhesive number (average number of oral streptococcuses adhesed on 1 buccal epithelial cell), adhesive index (AI) (percentage of buccal epithelial cells that adhesed more than 10 oral streptococcuses) and index of colonization resistance in points. The method is used to estimate the body's resistance in different diseases as predictive factor. It is based on an assessment of the number of microorganisms adsorbed on the surface of epithelial cells, stained by Romanovsky it and studied the correlation of oral microflora and the epithelial cells of the mucosa. The results of clinical trials were analyzed using a number of biostatistics methods. Thus the prevalence of caries process of the students from the stomatological faculty continues to be high. Reducing the frequency and intensity of periodontal disease in persons surveyed graduation rate indicates greater awareness of students of 5th year of study on the prevention and treatment of dental diseases. Established the absence of significant differences between the values of indicator colonization resistance ATSU based on research areas and groups of patients. This fact probably explains the high level of non-specific resistance stated in terms of response adsorption of microorganisms in the examined groups of students. For a more reasoned conclusions should increase the group surveyed and analyze the studied parameters in the dynamics of clinical and laboratory observations to form individual preventive and treatment measures for major dental disease of young people.